Ethical Reflections on the Practice of Pre-Election Polls in Indonesia - Samsul Maarif Mujiharto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2023)
This paper aims to connect the practice of pre-election polls to moral issues and democracy. Several studies have indicated that pre-election polls have grown to become essential pillars of democracy. The prediction capabilities of pre-election polls can help politicians arrange strategies to listen to the public's voice and win political contestation. However, since the practice of pre-election polls is not only scientific evidence but also political credential, it crosses the blurry boundary where they intersect one another. Consequently, this may exacerbate some pathologies of polls such as method corruption, data manipulation, bandwagon effect, and political mobilization. Focusing on the 2014 and 2019 Indonesia presidential elections, this paper suggests that ethical consideration to ensure the practice of pre-election polls is necessary for bringing the polls back as one of the prime pillars of democracy.